Mitral valve regurgitation due to annular dilatation caused by a huge and floating left atrial myxoma - Kaya, Mehmet; Ersoy, Burak; Yeniterzi, Mehmet (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
We describe a case of mitral valve annular dilatation caused by a huge left atrial myxoma obstructing the mitral valve orifice. A 50-year-old man presenting with palpitation was found to have a huge left atrial myxoma protruding into the left ventricle during diastole, causing severe mitral regurgitation. The diagnosis was made with echocardiogram. Transoesophageal echocardiography revealed a solid mass of 75 × 55 mm. During operation, the myxoma was completely removed from its attachment in the atrium. We preferred to place a mechanical heart valve after an annuloplasty ring because of severely dilated mitral annulus and chordae elongation. The patient had an uneventful recovery. Our case suggests that immediate surgery, careful evaluation of mitral valve annulus preoperatively is recommended.